Malawi Complementary Panel Survey (CPS) 2000-2002 - International Food Policy Research Institute (International Food Policy Research Institute, 2004)
The Complementary Panel Survey (CPS) is a continuation of the work undertaken by the Malawi Poverty Monitoring System (PMS) since 1997. Four rounds of the CPS were conducted between January 2000 and September 2002. The PMS itself was conceived as part of the Government of Malawi's Poverty Alleviation Programme (PAP) launched in 1994. The Policy Framework for PAP articulated the overall objective of the PMS as being to assist the government monitor poverty by collecting and analyzing data relevant to track progress in poverty reduction and to help guide the formulation of poverty alleviation policies and programs. The Malawi National Statistical Office, the National Economic Council (NEC) and the Center for Social Research of the University of Malawi along with the technical assistance of the International Food Policy Research Institute (IFPRI), a program encompassing the implementation of a regular detailed Integrated Household Survey (IHS) was designed. The resulting Complementary Panel Survey is based on the IHS sample and complementary to the IHS, and the poverty analysis of the data collected by the two survey programs. The IHS was to be conducted every three to five years, while the panel survey twice a year. The final sample size of the CPS in the first round was 758 households. The CPS dataset includes information on education; morbidity; food security and coping strategies; labour and employment; income, expenditures, and transfers. The questionnaire for the fourth round of the CPS was developed explicitly to allow a welfare indicator to be constructed that would be comparable to the welfare indicator developed in the poverty analysis of the 1997-98 Integrated Household Survey. This was necessary to allow the IHS data and poverty analysis to be linked to the CPS data in order to undertake an analysis of the dynamics of household welfare in the CPS sample between the IHS and the fourth round.